2014
DOI: 10.1016/s2214-109x(13)70179-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality in adolescents compared with women of other ages: evidence from 144 countries

Abstract: WHO, UN Population Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
227
2
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(250 citation statements)
references
References 17 publications
15
227
2
6
Order By: Relevance
“…Pregnancy in teenagers can result in adverse maternal outcome such as severe anemia or death and compromise their socio-economic opportunities [5]. Children from teenage mothers are more likely to be stunted at their second birthday, to develop glucose disorder and problems at school [3].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy in teenagers can result in adverse maternal outcome such as severe anemia or death and compromise their socio-economic opportunities [5]. Children from teenage mothers are more likely to be stunted at their second birthday, to develop glucose disorder and problems at school [3].…”
Section: Introductionmentioning
confidence: 99%
“…The mean gravida was 2 ± 1.6 [1][2][3][4][5][6][7][8][9] and the mean parity was 1 ± 1.5 [8]. Six patients (4.8%) had a past history of preeclampsia and 24 patients (19 %) had chronic HPT.…”
Section: Resultsmentioning
confidence: 99%
“…Developing countries account for 99% of all 289 000 global maternal deaths with sub-Saharan Africa (SSA) regions alone accounting for 62 % in 2013 [1,2]. Hypertension (HPT) during pregnancy is a worrying issue despite the implementation of strategies aiming to improve maternal and child health.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, the cesarean section rate was significantly lower in early adolescent mothers [3]. In contrast, recent data obtained from 144 countries indicated that, "excess mortality risk to adolescent mothers might be less than previously believed, and in most countries the adolescent maternal mortality ratio is low when compared with women older than 30 years" [4]. In this study, adolescence has been investigated as, and categorized into, three stages: early (11-13 years old), middle (14-16 years old) and late adolescence (17-19 years old) [5].…”
Section: Introductionmentioning
confidence: 87%